Towards a southern approach to sex work - Sultana, Habiba, author.
1 online resource
Keywords: This book delves into this almost unchartered territory, documenting the lived experiences of sex workers in Bangladesh, considering the complex realities of their day-to-day lives and the ways they negotiate their working conditions and relationships. Despite being the most common form of female deviance and criminality globally, we know very little about sex work in Asia and the global south. Drawing on feminist frameworks, it shows that the experiences of sex workers vary widely depending on the ways they enter the sex trade, their modes of operation, and relationships with significant others. Towards a Southern Approach to Sex Work contributes to feminist scholarship on sex work, by offering a much needed southern perspective, drawing on culturally specific data. It argues that the lived experience of sex workers comprises both victimhood and agency, deception and resilience, and that it is the management of these relationships that enable sex works to avoid social marginalization and alienation. An accessible and compelling read, this will appeal to students and scholars of criminology, sociology, gender studies, south Asian studies, cultural studies, social theory and policy makers. In addition, it will engage all those interested in learning more about how the sex trade operates in Bangladesh.